EXPLORING BLENDED TRAINING SCHEME TO IMPROVE EMPLOYEE TRAINING OUTCOMES: AN ASSESSMENT OF ORIENTATION TRAINING PROGRAMMES IN UNIVERSITY FOR DEVELOPMENT STUDIES - Antwi, E. A.; Tampah-Naah, C.; Buame, J. A. (UDS International Journal of Development, 2019)
Employee orientation training in the University for Development studies is effective in helping new employees learn about an organisation’s philosophy. The spread of the campuses of the University across three regions of Ghana, Northern, Upper East and Upper West regions offers a challenge for an effective orientation with the current training model. For efficiency, organisations must ensure that financial and human resources are allocated to develop the highest impact training strategies at the lowest cost. The problem of study sees as deficient the current orientation training programme for newly recruited staff of the University and therefore less effective in improving learners’ outcomes to achieve corporate objectives. A close look at interview reports at the Human Resource Unit and attitude of most staff of the University appears to suggest a lack of knowledge of Conditions of Service, Statutes of the University, Scheme of Work and even Schedule of Duties at the workplace. Some staff are unaware of requirements for their next promotion or when to apply for promotion. The findings revealed the ‘face to face’ orientation model of the University was not effective in improving learning outcomes. This paper reviewed literature on training and some learning methodologies. Recommendations are made to University management to re-think their current training model and to accept modifications that would improve learners’ outcomes and achieve corporate initiatives. A blended learning scheme comprising basic concepts of learning, integrated with method of instruction and technological delivery media is recommended. Keywords: Orientation training, blended learning, e-learning, work performance